Sara Levy's world : gender, Judaism, and the Bach tradition in enlightenment Berlin - Cypess, Rebecca; Sinkoff, Nancy, 1959- (Eastman studies in music ;, 2018)
"Sara Levy née Itzig (1761-1854), a salonnière, skilled performing musician, and active participant in enlightened Prussian Jewish society, played a powerful role in shaping the dynamic cultural world of late eighteenth- and early nineteenth-century Berlin. A patron and collector of music, she studied harpsichord with Wilhelm Friedemann Bach (1710-84) and commissioned musical compositions from both Friedemann and his brother Carl Philipp Emanuel Bach (1714-88). Archival evidence demonstrates Levy's position as an essential link in the transmission of the music of their father, Johann Sebastian Bach (1685-1750), and as a catalyst for the "Bach revival" of the early nineteenth century, which was led by her great-nephew Felix Mendelssohn. Sara Levy's World: Gender, Judaism, and the Bach Tradition in Enlightenment Berlin represents the first scholarly exploration of the cultural, political, and aesthetic contexts that shaped Levy's world. Bringing together leading scholars from the fields of musicology, Jewish Studies, history, literary studies, gender studies, and philosophy, this volume presents cutting-edge, multidisciplinary research on the numerous mutually reinforcing aspects of Levy's life and work"--Back cover